Role for structured telephone clinics in paediatric gastroenterology: reflections, lessons and patient feedback. Issue 1 (2nd February 2019) - Duncan, Hazel; Russell, Richard K
Abstract : Background: Telephone clinics have been established within our department to try and improve communication with families, limit waiting times and help face-to-face clinics run more efficiently. As part of the ongoing care needs for our patients and families it was felt important to determine if telephone clinics were meeting the needs of the young person and family as well as those of the health professional. Objective: To assess the effects of a structured consultant delivered telephone clinic. Method: Data were collected regarding patients who had a consultant telephone appointment between July 2016 and March 2017. Data collected include demographics and appointment reason. An evaluation questionnaire was sent to all parent/carer(s). Results: 25 clinics comprising 194 contacts, including 34 duplicate contacts. 120 questionnaires sent. 7/160 (4.3%) were new patients. The main contact reason was biopsy results after endoscopy (93/180; 52%). Failure to attend rate was significantly lower at 18/194 (9.2%) compared with failure to attend rate of 52/240 (21.6%) for a traditional clinic (p<0.001). 40/120 (33%) returned completed questionnaires, 25/40 (68.4%) reported the reason for appointment was test results. Travel time and school attendance were identified as main advantages. Mean parental rating score for the service was 8/10 with 21/40 (54%) scoring the service as 10/10. Conclusion: The initial results of this audit are promising. Structured telephone appointments have a key role in delivering patient care in paediatric gastroenterology and have benefits to health professional, parent/carer and patients. These clinics have now been widely adopted by all members of our department.